Children Car Seat / Nur Hidayah Amran - Amran, Nur Hidayah (2020)
Nowadays, the number of car road accident has significantly increased and thus this also cause an increasing number of children death. To reduce this number, our company has produce a protective and comfortable children car seat with the name NIÑAS & NIÑOS. The main function of this product is to provide safety to our children. The components that people can found in our car seat is light loud alarm, cooling fan, heating pad and also music compartments. All of this component have its own unique function to provide safety and also give cosiness to our little one. Moreover, our product is made of with a good materials such as polypropylene plastic and foam, polyester fabric and vinyls, rechargeable cooling fan and light alarm with LDR. In this product, our target market is mainly for children and also married people with children. This is because, as had been stated before this product is mainly create for the children. Due to its affordable price, this product will be sell to B40 and M40 people. Our estimation for our revenue in 3 years for this product is around RM2,055,748.86. There are so many children car seat with a well-known brand and uniqueness. However, our product has its own strength to compete with other famous brands. Some of our strength is our product is not for a new born only but we create this product for children up to 6 years old. Furthermore, it also affordable, lightweight and provide too much cosiness to the children. For the profitability, we will sell our product using E-Marketing which are through instagram and facebook. Moreover, we will use a media network to advertise our product. Through this methods, it will help us to achieve our target profit. Lastly, to make the flow of our company smooth, we have create a capable management team to help in making a perfect car seat. The management team include the Chief Executive Officer (CEO), Marketing Manager, Production Manager, Sales Manager, Human Resources Manager and Financial Manager. All of this position have its own responsibilities to ensure that this product is perfectly create.